Dynamic Groups Based Adaptive DTN Routing Algorithms in Social Networks - Jixing Xu; Jianbo Li; Lei You; Chenqu Dai (International Journal of Distributed Sensor Networks)
Due to the nonexistence of end-to-end path between the sender and the receiver in delay tolerant networks and mobile social networks, consequently successful message transmission faces great challenges. In this paper, an adaptive routing algorithm taking full use of gregariousness characteristics of moving nodes is proposed. We first abstract all social relationships and uniformly represent them using friendship. Then by dynamically dividing nodes into different social groups, we finish flooding message among the target social group where destination node resides. In addition, we propose a social group based flooding model and a message redundancy control model to select fewer but better relay nodes and further reduce message redundancy. Extensive simulations have been conducted based on the synthetic traces generated by working day movement model and the results show that the proposed routing algorithm can get a higher message delivery ratio and a lower overhead ratio compared to Bubble Rap, Epidemic, and ProPHET, thus proving a better routing performance.